2012
DOI: 10.1155/2012/580873
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CD63 Upregulation Induced by NSAIDs on Basophils and Monocytes in Patients with NSAID Hypersensitivity

Abstract: Background. An in vitro basophil activation test, based on the detection of CD63 upregulation induced by NSAIDs, has been described. Its clinical significance remains controversial. Objectives. In patients with a history of nonallergic NSAID hypersensitivity, stratified according to the severity of the symptoms, to assess with NSAIDs the predictive value of basophil (BAT) and monocyte (MAT) activation tests. Patients/Methods. Sixty patients who had NSAIDs-induced or exacerbated urticaria/angiooedema and 20 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 38 publications
0
26
0
4
Order By: Relevance
“…In a comparative study of the sensitivity of CD63 and CD203c in IgE-mediated amoxicillin allergies, CD203c sensitivity is superior to CD63 11. In contrast, patients with non-allergic NSAID hypersensitivity upregulate CD63 expression more frequently than CD203c expression 12. In this study, basophils of patients with cefaclor-induced anaphylaxis upregulated CD203c, but not CD63.…”
Section: Discussionmentioning
confidence: 50%
“…In a comparative study of the sensitivity of CD63 and CD203c in IgE-mediated amoxicillin allergies, CD203c sensitivity is superior to CD63 11. In contrast, patients with non-allergic NSAID hypersensitivity upregulate CD63 expression more frequently than CD203c expression 12. In this study, basophils of patients with cefaclor-induced anaphylaxis upregulated CD203c, but not CD63.…”
Section: Discussionmentioning
confidence: 50%
“…In confirmed IgE-mediated amoxicillin allergy, the sensitivity for CD203c was found to be far superior to that of CD63 (60 vs. 20 %) [22]. In contrast, the same group demonstrated that CD63 expression was up-regulated more frequently than CD203c in patients with non-allergic NSAID hypersensitivity [27]. In patients with venom hypersensitivity, CD203c and CD63 were found to have similar kinetics, with maximum expression detected after 20 min of allergen stimulation.…”
Section: Update On the Performance Of Basophil Activation Testsmentioning
confidence: 99%
“…In addition, 22 of these patients had hypotension, laryngeal edema, dyspnea, abdominal pain, vomiting, or diarrhea after NSAID intake. They found that the sensitivity among those patients without the visceral symptoms was only 21 %, but this increased to 64 % among those with more severe reactions [27]. Similarly, Korosec et al demonstrated that the BAT among NSAID-intolerant patients may only have diagnostic value for those with anaphylactoid reactions rather than those with asthma/rhinitis symptoms [30].…”
Section: Update On the Application Of Basophil Activation Testsmentioning
confidence: 99%
“…As displayed in tables, the technique has mainly been applied to document allergy to NMBAs (table 1) [8,9,10,11,12,13,14,15,16], antibiotics like β-lactam antibiotics and quinolones (table 2) [17,18,19,20,21,22,23,24,25,26,27,28,29,30], aspirin and other nonsteroidal anti-inflammatory drugs (NSAIDs; table 3) [31,32,33,34,35,36,37,38,39,40,41,42,43,44,45], and iodinated radiocontrast media (RCM; table 4) [46,47,48]. In general, the sensitivity of the assay varies between 50 and 60%, whereas specificity easily attains 80%, except for quinolones and NSAIDs (see below).…”
Section: Bat and Histaflow In Immediate Drug Hypersensitivitymentioning
confidence: 99%